Training On Making "Soybean Tempe" To Increase Family Income For Local Housewives In Silalas Village, Medan - Lusiah, Lusiah; Parulian, Edison; Menara Sari Saragih , Lenny; Tarwiyah, Tarwiyah; Wongsosudono, Corinna (International Journal Of Community Service, 2023)
This activity is a partnership-based UMKM development program where this program provides activities to provide tempe training to housewives located in Silalas Village, West Medan by bringing in resource persons who are UMKM assisted by the UMKM development program who also act as mentors for community members, especially mothers. households in the Silalas Village environment to foster entrepreneurial interest and provide ideas for business activities that can be carried out so as to improve the family's economy. Apart from that, the resource person can also share tips for successfully running a business using enthusiasm, tenacity and perseverance with housewives.